Dance images in the documentary films: its history and development - Kun, Yu; Yaakup, Hani Salwah; Syed Zainudin, Sharifah Sofiah; Mohammad Razi, Siti Aishah (Universitas Islam Riau Press, 2022)
Since its development, various types and forms have been introduced in documentaries. This includes the usage of dance images in the documentary. The existence of the dance video is used as a segment of the documentary to express the rich artistic image. Therefore, the use of dance images in documentaries needs to be treated rationally for the audience to understand its meaning. The audience has its own perception, and at the same time has its own cognition and understanding, and whether the audience understands the rhetoric of body language conveyed by the communicator. At the same time, the documentary does not lack the occurrence of the story, and the relationship between the dance image and the plot is also an issue that needs attention. However, the relationship between dance images and plots in documentaries is still debatable due to the lack of research done in this area. In this article, the focus will be given to the history and development of dance images in the documentary as a foundation of further study on this area. The discussion includes the history of dance images and the development of dance images from the perspective of visual narrative, visual vocabulary, imaging environment, and its relation to video technology & dance video.